The Influence of Volleyball Training on the Psychological Health Development of College Students - Xiaofan Hao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the impact of volleyball training on the mental health development of students, the author proposes a study on the impact of volleyball training on the mental health development of college students. A volleyball player from a sports university in a certain city, by using literature review, questionnaire, interview, and data statistics methods, factor analysis was conducted on the factors that affect the competition status of college volleyball players. A total of 90 questionnaires were distributed to athletes, with 85 questionnaires collected, with a recovery rate of 93%, 81 valid questionnaires were collected, with a response rate of 95%. Among the 90 factors that affect the smooth state of college volleyball players in competitions, there are 5 main common factors, namely "scientific and reasonable training before the competition", "mutual trust among teammates", "detailed understanding of opponents before the competition", "communication with teammates during the competition", and "positive and optimistic attitude during the competition". Through psychological training, volleyball players can achieve a high level of psychological preparation to meet the requirements of the competition. According to the individual situation of the team members and the needs of the game, appropriate psychological training methods are adopted to enable them to adjust and control their psychological state to adapt to the intense competition and perform at a high level. Therefore, it is necessary to grasp the psychological factors and training methods of volleyball players. A good psychological state plays an important role in winning training competitions for volleyball athletes, psychological state is an ideology that involves being completely and selflessly engaged in a task, and being able to fully or exceptionally demonstrate one's best level of physical activity. It is a way of evaluating the psychological level of volleyball players. The research also discussed the limitations and future directions for further research.